KEPENTINGAN RUSIA DI SAMUDRA ARKTIK MELALUI KEBIJAKAN FUNDAMENTALS OF STATE OF POLICY OF THE RUSSIAN FEDERATION POLICY IN THE ARCTIC IN THE PERIOD UP TO 2020 AND BEYOND - Rusiantama, Muhammad Prahaseno; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
This study aims to describe the interests of the Russian Government in the Arctic Ocean through its foreign policy using descriptive qualitative research methods. By describing the results of research in narrative form. Arctic Ocean is an area that has a lot of potential, especially for the countries around it. Russia, as one of the States near Arctic Ocean, carried out a controversial activity by conduction an expedition that ended with the country’s flag being plugged into the Arctic Ocean. The activity received response from various neighboring countries because Russia was deemed not to comply wilth the agreement between countries. Therefore, the researcher uses the framework of foreign policy and national interest in answering the reasons behind Russia’s national interest in the Arctic Ocean region. The research later found the answer that Russia has security interest and economic interest in the Arctic Ocean. Keywords: State Security, Foreign Policy, National Interest, Arctic Ocean, Natural Resource